PENERAPAN LINEAR PROGRAMMING MODEL PENUGASAN (ASSIGNMENT MODEL) DALAM MENGOPTIMALKAN ALOKASI ADMIN TOKO ONLINE GUNA MEMINIMALKAN WAKTU PROSES PESANAN: (Studi Operasional e-commerce Berbasis Komputasi QM for Windows) - Tasya Putri Regina Nadeak; Jhon Kristopel Manalu; Parapat Gultom (JURNAL ILMIAH PENELITIAN MAHASISWA, 2026)
Order fulfillment speed (order fulfillment time) is a key performance indicator (Key Performance Indicator/KPI) for online shop businesses to maintain marketplace algorithm ratings and customer loyalty. This study aims to optimally assign tasks among four online shop administrators (Admin 1, Admin 2, Admin 3, and Admin 4) to four types of daily workflows, namely Responding to Customer Chats, QC & Product Packing, Stock & Content Updates, and Handling Returns & Complaints. A quantitative approach was applied through the Assignment Model with the parameter of minimizing the average daily task completion time (in minutes) using QM for Windows software version 5. The input data was based on the recording of administrators' actual average working time during the twin date sale promotional period. The computational processing results using the Hungarian algorithm produced an optimal allocation decision that successfully reduced the total task processing time from 185 minutes to 130 minutes. This 29.7% reduction in operational duration proves the effectiveness of managerial decisions based on quantitative data in eliminating inefficiencies in digital retail businesses.